COMPARATIVE ANALYSIS OF FACTORS THAT ENCOURAGE FOREIGN DIRECT INVESTMENT IN SERBIA AND ROMANIA - Grandov, Zorka; Stankov, Biljana M; Roganović, Milijana M (International Journal of Economic Practice and Policy, 2015)
The importance of foreign direct investment, FDI in rapid economic recovery and further development of Serbia and Romania encouraged the study of these issues in particular through trend research in FDI inflows over the past years, analyzing their structure and sectoral distribution, description of the investment environment and investment incentives. Since 2007, Romania became a full member of the EU and Serbia in 2012 was granted candidate status for membership, thus these countries have become very attractive investment destinations. By applying desk method and method of content analysis in order to collect relevant research data as well as by using descriptive and comparative research methods, defined general and specific research hypotheses will be tested. The scientific problem highlights the importance and many advantages of FDI as one of the most desirable forms of foreign capital investment in Serbia and Romania, and discoversthe factors that attract foreign investors in the mentioned countries and lead them to make an investment decision. The subject of this study is to investigate the movements of FDI over the past twenty years, their structure by economic activities, different factors of geographic, economic and socio-political nature which affect the attractiveness of the analyzed countries as investment destinations as well as tax and non-tax incentives which have a strong impact on foreign investors in choosing investment destination. The main objectives of this research are establishing economic sectors that have so far attracted the largest number of foreign investors, highlighting the similarities and differences in tax and non-tax investment incentives among the analyzed countries as well as comparison of trends in Serbia as a candidate for EU membership with the European averages by highlighting key elements that make both analyzed countries attractive investment destinations.
Keywords: foreign investors; foreign direct investments (FDI); investment incentives; investment destination; Serbia; Romania; European Union (EU)